IDENTIFIKASI TENTANG PENGGUNAAN MEDIA PEMBELAJARAN PADA MATA PELAJARAN EKONOMI MATERI AKUNTANSI KELAS XI IPS DI SMA NEGERI 1 BABAT LAMONGAN - JULI ENDRAWATI (Jurnal Pendidikan Akuntansi (JPAK), 2013)
Learning is an activity that involves a person in an effort to acquire the knowledge and skills to utilize various sources to learning. Use of the tools instructional media is necessary to assist in the learning process and facilitate the delivery of the subject matter, for it is done research that aims to identify instructional media are to be used by teachers accounting subjects in class XI IPS SMA Negeri 1 Babat Lamongan and find out the reason why the teachers use instructional media in learning activities. This research is a descriptive research. Techniques of data collection using interviews and documentation while research instrument uses expert interviews and a review of media sheets. Based on the analysis of data using descriptive analysis techniques and quantitative descriptive analysis techniques to determine the feasibility study media, the result that teachers use instructional media powerpoint which shows that the media is fit for use in the classroom learning activities accounting with a percentage of 63.99%. Keyword : descriptive research, instructional media, accounting cycle services company